Physical and mechanical properties of lightweight concrete based on gypsum binders and peat vermiculite granules - Д. С. Gorkoltseva; N. O. Kopanitsa (Вестник СибАДИ, 2022)
Introduction. An analysis of the literature and experimental data on the resource provision of the construction market has shown that the development of new and effective materials with improved quality parameters is an urgent task, and in the long term will serve as an impetus for the development of the building materials market. Currently, the peat industry in Russia is experiencing a serious decline in the extraction of peat raw materials, the reserves of which are practically inexhaustible. One of the possible ways to develop this industry in the Tomsk region can be the organisation of the production of competitive structural, heat-insulating and heat-insulating materials using local raw materials, namely lowland peat and vermiculite, which will improve the economic prestige of the region, create new enterprises and jobs.Materials and methods. The studies using the methods and tests set out in national standards were carried out. The measurement of the obtained material density was carried out in accordance with GOST 17177-94. The determination of the samples strength in compression and in bending was carried out in accordance with GOST 23789-2018. The determination of the moisture content percentage of the samples was carried out in accordance with GOST 23789-2018.Results. The results of the research made it possible to determine the basic requirements for the designed composition of lightweight concrete based on gypsum binders and peat vermiculite granules. The relationship between the strength characteristics and density of lightweight concrete has been studied, it has been established that at average density values in the range of 530-850 kg/m3, the resulting material meets the basic technical requirements of heat-insulating lightweight concrete (GOST 25820-2014).Discussion and conclusions. In the work, experimental studies determined the rational ratio of the components of lightweight concrete based on gypsum binder and peat vermiculite granules, at which the maximum value of their strength is achieved at a minimum average density. Based on the data obtained, it was found that in order to achieve the necessary physical and mechanical properties of lightweight concretes based on gypsum binders, the optimal size of peat-vermiculite granules should be no more than 5 mm.